Development of Computed Tomography Scanner Application: Prototype Model Approach - Yusoff, M.S.M; Sulaiman, R.; Shafinah, K.; Fatihah, Ramli; Abdullah, J. (Institute of Advanced Engineering and Science, 2016)
M.S.M. Yusoff1, R. Sulaiman1, K. Shafinah2,3, R. Fatihah2,4, J. Abdullah5